CLINICAL EVALUATION OF THE EFFECTIVENESS OF A COMPLEX OINTMENT PREPARATION WITH COLLAGENASE IN THE COURSE OF PURULENT NECROTIC PROCESSES OF SOFT TISSUES - Khimich, Sergii; Rautskis, Victor; Stoianovskyi, Ihor; Malyshevskyi, Ihor; Prevar, Anatoliy; Katelian, Olena (Eastern Ukrainian Medical Journal, 2025)
Background. Traditional methods of treating purulent wounds in experimental and clinical surgery are often ineffective and there is a need to improve them and develop new methods and tools, including the use of drugs for biological cleansing of necrotic tissues in wounds. The aim of the study was to conduct a clinical evaluation of gel agent “Iruksan” in the treatment of patients with infected, purulent wounds and necrotic processes of soft tissues. Materials and methods. Seventy-eight patients with infected, purulent wounds and necrotic processes were observed. They were divided into the main group (37 patients, who received complex treatment with a collagenase-based therapeutic mixture (Iruksan)) and the comparison group (41 patients), who received treatment with Levomekol ointment. The average age of the patients was 52.3±17.1 years. Fifty-one patients (65.4% of the examined) were diagnosed with abscess, abscessing furuncle, carbuncle, or abscessing hidradenitis. Phlegmon was observed in 12 patients (15.4%), and 15 patients (19.3%) had suppurative and infected postoperative wounds after surgical interventions. In addition, an analysis of the use of Iruksan was conducted in obese patients who developed purulent-necrotic complications after abdominal surgery and in patients with necrotizing fasciitis. Results. In the main group, pain syndrome resolved on average after 4.2±1.2 days, while in the comparison group, it resolved on average after 5.0±1.7 days (this difference is not statistically significant (p=0.094)), but the reduction in the duration of pain in the study group shows a positive trend. The use of Iruxan allowed to cleanse the wound in 4.1±1.7 days in the main group, while in the comparison group, wound cleansing took 5.9±1.9 days (p=0.00012). Wound epithelialization in patients in the main group occurred after 7.8±2.1 days, and in patients in the comparison group – after 8.4±1.3 days (p=0.0187). Thus, it becomes clear that faster cleansing of the wound from dead tissue occurs due to collagenase, a proteolytic enzyme, which is a part of Iruxan. Conclusions. A complex preparation containing collagenase (Iruxan) showed positive results when used to treat patients with purulent-necrotic processes in soft tissues, as well as in the treatment of patients with purulent-necrotic complications after surgical interventions on the abdominal organs in obese individuals, which, in turn, opens up prospects for further in-depth study and application of this drug in such patients. The use of Iruksan in combination with VAC therapy is also possible and makes it possible to significantly improve the treatment outcomes of patients with necrotizing fasciitis and purulent-necrotic pathology in patients with obesity.